Intestinal bile acid malabsorption in cystic fibrosis. Issue 8 (August 1993) - O'Brien, S; Mulcahy, H; Fenlon, H; O'Broin, A; Casey, M; Burke, A; FitzGerald, M X; Hegarty, J E
Abstract : This study aimed at examining the mechanisms participating in excessive faecal bile acid loss in cystic fibrosis. The study was designed to define the relation between faecal fat and faecal bile acid loss in patients with and without cystic fibrosis related liver disease; to assess terminal ileal bile acid absorption by a seven day whole body retention of selenium labelled homotaurocholic acid (SeHCAT); and to determine if small intestinal bacterial overgrowth contributes to faecal bile acid loss. The study population comprised 40 patients (27 men; median age 18 years) with cystic fibrosis (n = 8) and without (n = 32) liver disease and eight control subjects. Faecal bile acid excretion was significantly higher in cystic fibrosis patients without liver disease compared with control subjects (mean (SEM) 21.5 (2.4) and 7.3 (1.2) micromoles/kg/24 hours respectively; p < 0.01) and patients with liver disease (7.9 (1.3) micromoles/kg/24 hours; p < 0.01). No correlation was found between faecal fat (g fat/24 hours) and faecal bile acid (micromoles 24 hours) excretion. Eight (33%) of cystic fibrosis patients had seven day SeHCAT retention < 10% (normal retention > 20%). SeHCAT retention in cystic fibrosis patients with liver disease was comparable with control subjects (30.0 (SEM) 8.3% v 36.8 (5.9)%; p = NS) while SeHCAT retention in cystic fibrosis patients who did not have liver disease was significantly reduced (19.9 (3.8); p < 0.05). Although evidence of small bowel bacterial overgrowth was present in 40% of patients no relation was found between breath hydrogen excretion, faecal fat, and faecal bile acid loss. The results are consistent with the presence of an abnormality in terminal ideal function in patients with cystic fibrosis who do not have liver disease and that a defect in the ileal absorption of bile acids may be a contributory factor to excessive faecal bile acid loss. Faecal bile acid loss in cystic fibrosis is unrelated to the presence of intraluminal fat or intestinal bacterial overgrowth.